Patient and primary care physician characteristics associated with billing incentives for chronic diseases in British Columbia: a retrospective cohort study - McGrail, Kimberlyn (CMAJ Open, 2020)
BACKGROUND: Incentive payments for chronic diseases in British Columbia were intended to support primary care physicians in providing more comprehensive care, but research shows that not all physicians bill incentives and not all eligible patients have them billed on their behalf. We investigated patient and physician characteristics associated with billing incentives for chronic diseases in BC. METHODS: We conducted a retrospective cohort analysis using linked administrative health data to examine community-based primary care physicians and patients with eligible chronic conditions in BC during 2010–2013. Descriptive analyses of patients and physicians compared 3 groups: no incentives in any of the 4 years, incentives in all 4 years, and incentives in any of the study years. We used hierarchical logistic regression models to identify the patient- and physician-level characteristics associated with billing incentives. RESULTS: Of 428 770 eligible patients, 142 475 (33.2%) had an incentive billed on their behalf in all 4 years, and 152 686 (35.6%) never did. Of 3936 physicians, 2625 (66.7%) billed at least 1 incentive in each of the 4 years, and 740 (18.8%) billed no incentives during the study period. The strongest predictors of having an incentive billed were the number of physician contacts a patient had (odds ratio [OR] for > 48 contacts 134.77, 95% confidence interval [CI] 112.27–161.78) and whether a physician had a large number of patients in his or her practice for whom incentives were billed (OR 42.38 [95% CI 34.55–52.00] for quartile 4 v. quartile 1). INTERPRETATION: The findings suggest that primary care physicians bill incentives for patients based on whom they see most often rather than using a population health management approach to their practice.